The effects of information source and eHealth literacy on consumer health information credibility evaluation behavior - Chang, Yung-Sheng; Zhang, Yan; Gwizdka, Jacek (Computers in human behavior, 2021)
Health consumers can easily access information on the Internet. The quality of online health information varies and overall is concerning. The definition of eHealth literacy implies that consumers' ability to evaluate online health information varies with their eHealth literacy. A lab-based experiment was conducted to investigate how information source and consumers’ eHealth literacy affect their use of different types of indicators and criteria in evaluating the credibility of online health information. Credibility evaluation was viewed as a process of utilizing criteria to interpret webpage indicators. Twenty-five participants each viewed a total of 15 webpages from government, commercial, and online forum sources (five from each). Gaze-cued retrospective think-aloud was employed to elicit the indicators and criteria that participants used to evaluate the webpages. The findings showed that content-related indicators and criteria were used the most in credibility evaluation across different information sources. Participants used source indicators more often than design indicators in evaluating government websites and used design criteria more often than individual factors in evaluating commercial websites. eHealth literacy did not significantly affect credibility evaluation but showed a marginally significant interaction effect with information sources on the number of indicators used. The results enhance our understanding of factors influencing consumer online health information evaluation behavior. •Source type significantly influences the use of quality indicators and criteria.•Content and source indicators were used with similar frequency for governmental sources.•Content indicators were used the most and design indicators the least for online forums.•Design criteria were used as frequently as source criteria for commercial sources.•eHealth literacy had a marginally significant effect on credibility evaluation.